Editorial for issue 3-2017: 65 years of the Military Technical Courier – acknowledgments - Gaćeša, Nebojša N. (Vojnotehnički glasnik / Military Technical Courier, 2017)
This editorial marks the jubilee which the scientific journal Military Technical Courier celebrates in 2017 - 65 years of regular and continuous publication. On this occasion, the Editorial Office expresses gratitude to individuals and institutions who have contributed most to the progress and success of the journal.
Keywords: Military Technical Courier; scientific journal; jubilee; sixty fifth anniversary; acknowledgments